2012
DOI: 10.1007/s00428-012-1259-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine differentiation does not have independent prognostic value in conservatively treated prostate cancer

Abstract: In vitro studies have implicated neuroendocrine differentiation in the development of hormone resistant prostate cancer following administration of androgen blockers. Studies on clinical material are equivocal. We wished to understand the significance of neuroendocrine differentiation in our large and well-characterised cohort of clinically localised prostate cancer, treated conservatively. Immunohistochemical expression of chromogranin-A was assessed semi-quantitatively on tissue samples of 806 patients in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
1
27
1
Order By: Relevance
“…Until recently, there has been considerable debate regarding the definition and classification of NEPC, which has resulted in contradictory reports regarding its clinical significance . In 2013, the Prostate Cancer Foundation assembled a working committee to address this issue and proposed a new pathological classification of NEPC .…”
Section: Definition and Classification Of Nepcmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, there has been considerable debate regarding the definition and classification of NEPC, which has resulted in contradictory reports regarding its clinical significance . In 2013, the Prostate Cancer Foundation assembled a working committee to address this issue and proposed a new pathological classification of NEPC .…”
Section: Definition and Classification Of Nepcmentioning
confidence: 99%
“…Until recently, there has been considerable debate regarding the definition and classification of NEPC, which has resulted in contradictory reports regarding its clinical significance. 12,16 In 2013, the Prostate Cancer Foundation assembled a working committee to address this issue and proposed a new pathological classification of NEPC. 17 The new classification consisted of: (i) usual prostate adenocarcinoma with NE differentiation; (ii) adenocarcinoma with Paneth cell NE differentiation; (iii) carcinoid tumor; (iv) small cell carcinoma; (v) LCNEC; and (vi) mixed NE carcinoma-acinar adenocarcinoma.…”
Section: Definition and Classification Of Nepcmentioning
confidence: 99%
“…Typical markers used to identify neuroendocrine differentiation (NED) in tumor tissue are neuron specific enolase (NSE), chromogranin A (CgA) and synaptophysin (Syp). 1 - 3 Neuroendocrine differentiation, measured by one or more of those markers, has been associated with disease progression 4 or poor survival in prostate cancer 5 , but up to now its prognostic value has not been clarified because of controversial results 6 ; 7 , 8 . However, Epstein et al 9 have recently suggested using neuroendocrine markers to better characterize and classify NED in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This has allowed precise examination of p53, CD147 and other markers in the context of structural rearrangements in prostate cancer as well as robust validation of new findings [99,100]. Other groups have similarly, through large consortia (notably the transatlantic group), exploited archival clinical tissue to produce large tissue arrays for biomarker studies [101,102]. These arrays have been based usually on surgically derived samples from RP or transurethral resection because of the abundance of tissue.…”
Section: Approach To Investigating Treatment Stratification Markersmentioning
confidence: 99%